APPLICATION OF FRICTION WELDING FOR PUMP DESIGN AND MANUFACTURING: A COMPREHENSIVE REVIEW - Haq, Muhammad Alfath Ziaul; Widodo, Agung; Saputra, Howard (International Journal of Mechanical Engineering Technologies and Applications, 2024)
The discussion regarding the balance between economical and performance for the pump design and manufacturing has been increasing in recent years. Of many intelligent innovations, the use of less costly materials for pump shaft is an interesting solution for the pump design. This solution can also be achieved by selecting less costly materials made from metal. Then, the less costly metal connected to electrical motor is joined with a more costly metal connected to the pump. Since both metals can be difference ones, an advance welding process to join both metals is then required. The friction welding process is expected to fulfill this requirement. In the friction welding, heat is generated during friction between these two dissimilar metals. The generated heat should achieve particular temperatures so that the two dissimilar metals can be joined. There are three types of friction welding, e.g. the stir friction welding, the linear friction welding and the continuous drive friction welding, which can be selected to join these two dissimilar metals. This paper is based on the authors’ experience and literature review to discuss the application of friction welding for the pump design and manufacturing.